Persepsi Siswa Terhadap Pemanfaatan Media Pembelajaran Audio Visual untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS Kelas IX di SMP Swasta Talitakum Medan - Neksen Sihotang; Manullang, Dapot Tua; Siahaan, Mian (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe: 1) To describe the use of audio-visual media in social studies learning for grade IX students at SMP Swasta Talitakum Medan. 2) To describe the perceptions of grade IX students towards the use of audio-visual media in social studies learning at SMP Swasta Talitakum Medan. This research is a qualitative study. The research was conducted at SMP Swasta Talitakum Medan. on July 30 to August 2, 2024. The subjects of this study were the Principal, Grade X Teachers, and Grade X Students. Data collection techniques were carried out using observation, interviews and documentation. Activities in qualitative data analysis using an interactive model, namely data collection (collection), data reduction (reduction), data presentation (display), and drawing conclusions (conclusion drawing). This study aims to see students' perceptions of the application of audiovisual learning media in social studies learning subjects. This research is a descriptive qualitative study where this study will analyze the opinions of 17 students and 5 teachers who were used as samples. In this study, interviews and questionnaires were used to collect data on the perception of the results of the study were students towards the use of audio-visual media. Examining the data descriptive method was used. students' perceptions of the application of audio-visual learning media make it easier for students to understand the concepts of social studies learning are at a good level where students agree that the application of audio-visual learning media makes it easier for students to understand mathematical concepts. In addition, students also stated that the use of audio-visual learning media can make learning more interesting, and stated that the use of audio-visual learning media can provide a clearer picture of mathematics learning materials.